Toward New Horizons : Arab Economic Transformation amid Political Transition - Finger, Harald (Departmental Papers; Departmental Paper, 2014)
The changing political landscape in the Arab world has created opportunities for economic transformation by tackling long-standing economic issues. Nevertheless, three years after the onset of political transition, implementing necessary economic policies has proven to be challenging. This paper lays out key elements of economic policy reform for Arab countries in transition.